FOSTERING STUDENTS’ EXPERIENCES IN ENGLISH WRITING WITH MICROBLOGGING IN TWITTER - Pham Thi Thu Hien (ENGLISH, 2019)
Twitter and Microblogging are two separate entities but completes each other. Both of them can be used as language learning tools and their potential has been proved by several scholars. This study tries to examine students’ experiences in integrating microblogging with twitter. It is also study about the beneficial roles of microblogging with Twitter in language learning, its relation to writing, and its appropriateness in language learning. This study employs a qualitative research methodology, and case study as its research design. Semi-structured interviews and questionnaires were employed in this study to find out about participants' views about microblogging and Twitter. From this study, it can be concluded that the participants of the study underwent various experiences during the implementation of microblogging with Twitter. They also felt that microblogging with Twitter at some point advantages them to systematically arrange their ideas, and allows them to choose appropriate diction of their ideas. They also stated that Twitter can be an appropriate means in language learning, especially in English writing.